1976
DOI: 10.1111/j.2044-8295.1976.tb01545.x
|View full text |Cite
|
Sign up to set email alerts
|

The Components of the Poggendorff Illusion

Abstract: An explanation of the Poggendorff misalignment illusion in terms of three basic components, the horizontal-vertical, longitudinal-transverse and obtuse angle effects, is proposed. It is argued that these effects amy either singly or jointly give rise to an apparent elongation- contraction of the space between the aligned elements with consequent change in apparent oblique direction. Experimental evidence for the involvement of the three components in various combinations and for modification of perceived direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 8 publications
(16 reference statements)
2
49
0
Order By: Relevance
“…The third outcome indicates that the HV spatial anisotropy contributes slightly to the misalignment effect. This finding is strongly supported by experiments with a pair of oblique lines (Day, 1973a) and the Poggendorff figure with vertical and horizontal parallels (Day & Dickinson, 1976). It will be assumed henceforth that the HV component also contributed to the effects in Experiments 1 and 2.…”
Section: Discussionsupporting
confidence: 72%
“…The third outcome indicates that the HV spatial anisotropy contributes slightly to the misalignment effect. This finding is strongly supported by experiments with a pair of oblique lines (Day, 1973a) and the Poggendorff figure with vertical and horizontal parallels (Day & Dickinson, 1976). It will be assumed henceforth that the HV component also contributed to the effects in Experiments 1 and 2.…”
Section: Discussionsupporting
confidence: 72%
“…These results seem consistent with the perceptual compromise hypothesis in the modified version proposed above. (3) Concerning the explanations of the standard Poggendorff illusion in terms of modifications of the space between the parallels as a consequence of an apparent vertical elongation or horizontal shortening of the space itself (Day & Dickinson, 1976), our results can be viewed as preliminary. A direct measurement of the modifications of the apparent size of the space between the parallels would be required, but has not yet been accomplished.…”
Section: Discussionmentioning
confidence: 94%
“…In any case, the alignment error still present in the control condition seems to point out the occurrence of a general alignment error concerning the oblique orientation, or of an apparent elongation of the vertical extent between the obliques, although it is less evident than in Experiment I (d. Appelle, 1972;Bouma & Andriessen, 1968;Day & Dickinson, 1976).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical form of the Poggendorff illusion refers to the apparent misalignment of two objectively collinear oblique lines separated by a pair of vertical lines, as in Figure lAo Although it is frequently classified as an illusion of direction, several investigators (Day & Dickinson, 1976;Greist-Bousquet & Schiffman, 1981bPressey, 1971;Quina-Holland, 1977;Zanuttini, 1976) have suggested that the Poggendorff misalignment may be due, at least in part, to the apparent contraction of the distance between the parallels. Recently, Schiffman (1981b, 1985), following the early work of Judd (1899), proposed that the underestimation of interparallel extent is caused by the relative influence of the amputated forms of the wings-out and wings-in Miiller-Lyer figure contained within the Poggendorff figure, as shown in Figures IB and lC with the transversals and in Figures ID and IE without the transversals, respectively.…”
mentioning
confidence: 99%